Control of double-joint arm posture in adults with unilateral brain damage - Mihaltchev, P.; Archambault, P. S.; Feldman, A. G.; Levin, M. F. (Experimental brain research, 2005)
It has been suggested that multijoint movements result from the specification of a referent configuration of the body. The activity of muscles and forces required for movements emerge depending on the difference between the actual and referent body configurations. We identified the referent arm configurations specified by the nervous system to bring the arm to the target position both in healthy individuals and in those with arm motor paresis due to stroke. From an initial position of the right arm, subjects matched a force equivalent to 30% of their maximal voluntary force in that position. The external force, produced at the handle of a double-joint manipulandum by two torque motors, pulled the hand to the left (165 degrees ) or pushed it to the right (0 degrees ). For both the initial conditions, three directions of the final force (0 degrees , +20 degrees , and -20 degrees ) with respect to the direction of the initial force were used. Subjects were instructed not to intervene when the load was unexpectedly partially or completely removed. Both groups of subjects produced similar responses to unloading of the double-joint arm system. Partial removal of the load resulted in distinct final hand positions associated with unique shoulder-elbow configurations and joint torques. The net static torque at each joint before and after unloading was represented as a function of the two joint angles describing a planar surface or invariant characteristic in 3D torque/angle coordinates. For each initial condition, the referent arm configuration was identified as the combination of elbow and shoulder angles at which the net torques at the two joints were zero. These configurations were different for different initial conditions. The identification of the referent configuration was possible for all healthy participants and for most individuals with hemiparesis suggesting that they preserved the ability to adapt their central commands-the referent arm configurations-to accommodate changes in external load conditions. Despite the preservation of the basic response patterns, individuals with stroke damage had a more restricted range of hand trajectories following unloading, an increased instability around the final endpoint position, altered patterns of elbow and shoulder muscle coactivation, and differences in the dispersion of referent configurations in elbow-shoulder joint space compared to healthy individuals. Moreover, 4 out of 12 individuals with hemiparesis were unable to specify referent configurations of the arm in a consistent way. It is suggested that problems in the specification of the referent configuration may be responsible for the inability of some individuals with stroke to produce coordinated multijoint movements. The present work adds three findings to the motor control literature concerning stroke: non-significant torque/angle relationships in some subjects, narrower range of referent arm configurations, and instability about the final position. This is the first demonstration of the feasibility of the concept of the referent configuration for the double-joint muscle-reflex system and the ability of some individuals with stroke to produce task-specific adjustments of this configuration.